Implementasi Pemuridan dalam Efesus 4:11-16 bagi Pertumbuhan Rohani Jemaat di Masa Kini - Paulus Kunto Baskoro; Indra Anggiriati (Sekolah Tinggi Teologi Nusantara, 2021)
Discipleship is the message of the Lord Jesus in the great commission to go to make disciples of all nations. Many Christians are just regular spectators and congregants. In fact, many churches are not very serious about the church. So that it does not implement the concepts of discipleship and causes the church to not grow or mature spiritually. The spirituality of the congregation that does not grow has many negative effects on the movement of God's church. It can even be said that a congregation whose spirituality does not grow will hinder God's work from growing tremendously. In fact, discipleship is the most important part of the life of God's church, especially in the spiritual growth of the congregation. In fact, the survey has shown that churches with a strong focus on discipleship will produce the maximum strength of the church. This is the background of an understanding of discipleship which has an impact on the spiritual growth of the congregation. This discussion will be carried out by observing some of the spiritual attitudes of believers who are discipled or who are not. The context for the discussion of discipleship is Ephesians 4: 11-16. As well as observations using the literature study method to sharpen the understanding of discipleship that brings the spiritual growth of the congregation. All of this aims to provide practical steps when discipleship occurs very effectively in a church which is carried out by church leaders, it will produce a strong spiritual life of the congregation and a strong church. A lot of student multiplication was taking place. The name of God is glorified and becomes awesome. Abstrak:Pemuridan merupakan pesan Tuhan Yesus dalam amanat agung untuk pergi menjadikan semua bangsa murid Yesus. Banyak orang Kristen hanya menjadi penonton dan jemaat biasa. Bahkan banyak gereja yang sangat tidka serius memperhatikan gereja. Sehingga tidak melaksanakan konsep-konsep pemuridan dan menyebabkan jemaat tidak bertumbuh atau dewasa rohani. Rohani jemaat yang tidak bertumbuh menjadikan banyak efek negatif bagi kegerakan gereja Tuhan. Bahkan bisa dikatakan jemaat yang rohaninya tidka bertumbuh akan menghambat pekerjaan Tuhan makin berkembang dengan dahsyat. Padahal pemuridan menjadi bagian terpenting dalam kehidupan gereja Tuhan, terutama dalam pertumbuhan rohani jemaat. Bahkan survey membuktikan gereja-gereja yang fokus pemuridannya kuat akan menghasilkan kekuatan gereja yang maksimal. Hal ini yang melatarbelakangi sebuah pemahaman tentang pemuridan yang berdampak kepada pertumbuhan rohani jemaat. Pembahasan ini akan dilaksanakan dengan metode pengamatan terhadap beberapa sikap hidup rohani orang percaya yang dimuridkan atau yang tidak dimuridkan. Konteks pembahasan pemuridan tertuju kepada Efesus 4:11-16. Serta juga pengamatan menggunakan metode studi literatur pustaka untuk mempertajam pengertian tentang pemuridan yang membawa pertumbuhan rohani jemaat. Semua ini bertujuan untuk memberikan langkah-langkah praktis ketika pemuridan terjadi sangat efektif dalam sebuah gereja yang dilakukan oleh para pemimpin gereja, maka akan menghasilkan kehidupan rohani jemaat yang kuat dan gereja yang kuat. Banyak multiplikasi murid-murid yang terjadi. Nama Tuhan dipermuliakan serta menjadi dahsyat.